STUDIES OF POTASH BEARING EVAPORITE BASINS OF KOHAT KARAK SALT RANGE, NWFP PAKISTAN - ALAUDDIN, M.; KHAN, ARJUMAND; MASOOD, HAJRA; BEGUM, FOZIA; KHATIAK, M.A.; KHAN, M. ASHRAF (Biological Sciences - PJSIR, 2022)
Potash-bearing minerals occur in nature with common salt and usually deposited in the evaporite basin on evaporation of brine water. In view of the huge deposits of common salt in Pakistan, particularly in Kohat-Karak evaporite basin, NWFP; investigations to locate the potash deposits in the common salt of the area were undertaken. The geology of the potash bearing deposits reveal their occurance in the form of lenticular beds associated with rock salts. The present study has successfully brought into focus areas of potash concentration in the above area which after refining may be exploited to meet the requirement of potash for fertilizer.